Antarctic benthic diatoms after 10 months of dark exposure: consequences for photosynthesis and cellular integrity - Handy, Jacob; Juchem, Desirée; Wang, Qian; Schimani, Katherina; Skibbe, Oliver; Zimmermann, Jonas; Karsten, Ulf; Herburger, Klaus (Frontiers in Plant Science, 2024)
Antarctic algae are exposed to prolonged periods of extreme darkness due to polar night, and coverage by ice and snow can extend such dark conditions to up to 10 months. A major group of microalgae in benthic habitats of Antarctica are diatoms, which are key primary producers in these regions. However, the effects of extremely prolonged dark exposure on their photosynthesis, cellular ultrastructure, and cell integrity remain unknown. Here we show that five strains of Antarctic benthic diatoms exhibit an active photosynthetic apparatus despite 10 months of dark-exposure. This was shown by a steady effective quantum yield of photosystem II (Y[II]) upon light exposure for up to 2.5 months, suggesting that Antarctic diatoms do not rely on metabolically inactive resting cells to survive prolonged darkness. While limnic strains performed better than their marine counterparts, Y(II) recovery to values commonly observed in diatoms occurred after 4-5 months of light exposure in all strains, suggesting long recovering times. Dark exposure for 10 months dramatically reduced the chloroplast ultrastructure, thylakoid stacking, and led to a higher proportion of cells with compromised membranes than in light-adapted cells. However, photosynthetic oxygen production was readily measurable after darkness and strong photoinhibition only occurred at high light levels (>800 µmol photons m-2 s-1). Our data suggest that Antarctic benthic diatoms are well adapted to long dark periods. However, prolonged darkness for several months followed by only few months of light and another dark period may prevent them to regain their full photosynthetic potential due to long recovery times, which might compromise long-term population survival.